The contribution of α4β2 and non-α4β2 nicotinic acetylcholine receptors to the discriminative stimulus effects of nicotine and varenicline in mice - de Moura, Fernando B.; McMahon, Lance R. (Psychopharmacology, 2017)
Rationale The extent to which non-α4β2 versus α4β2* nAChRs contribute to the behavioral effects of varenicline and other nAChR agonists is unclear. Objectives The purpose of this study was to characterize the discriminative stimulus effects of varenicline and nicotine using various nAChR agonists and antagonists to elucidate possible non-α4β2 nAChR mechanisms. Methods Separate groups of male C57BL/6J mice were trained to discriminate varenicline (3.2 mg/kg) or nicotine (1 mg/kg). Test drugs included mecamylamine; the nAChR agonists epibatidine, nicotine, cytisine, varenicline, and RTI-102; the β2-containing nAChR antagonist dihydro-β-erythroidine (DHβE); the α7 nAChR agonist PNU-282987; the α7 antagonist methyllycaconitine (MLA); the α3β4 antagonist 18-methoxycoronaridine (18-MC); and the non-nAChR drugs midazolam and cocaine. Results In nicotine-trained mice, maximum nicotine-appropriate responding was 95% nicotine, 94% epibatidine, 63% varenicline, 58% cytisine, and less than 50% for RTI-102, PNU-282987, midazolam, and cocaine. In varenicline-trained mice, maximum varenicline-appropriate responding was 90% varenicline, 86% epibatidine, 74% cytisine, 80% RTI-102, 50% cocaine, and 50% or less for nicotine, PNU-282987, and midazolam. Drugs were studied to doses that abolished operant responding. Mecamylamine antagonized the discriminative stimulus effects, but not the rate-decreasing effects, of nicotine and varenicline. DHβE antagonized the discriminative stimulus and rate-decreasing effects of nicotine but not varenicline in either the nicotine or varenicline discrimination assays. The discriminative stimulus, but not the rate-decreasing, effects of epibatidine were antagonized by DHβE regardless of the training drug. Conclusions These results suggest that α4β2* nAChRs differentially mediate the discriminative stimulus effects of nicotine and varenicline, and suggest that varenicline has substantial non-α4β2 nAChR activity.